Poverty: A central barrier to the implementation of the UN Sustainable Development Goals. Issue 125 (November 2021) - Leal Filho, Walter; Lovren, Violeta Orlovic; Will, Markus; Salvia, Amanda Lange; Frankenberger, Fernanda
Abstract: Poverty is one of the central elements in the transformative promise of the 2030 Agenda: leave no one behind. Ending poverty in all forms and everywhere is the first Sustainable Development Goal (SDG) and much can be discussed about its impact on several other sustainability elements. In this context, this paper explores the role of poverty and why it poses a central barrier in the implementation of the SDGs in developing countries. The research questions intended to assess: i) to which extent poverty is seen as a sustainability challenge and properly included in governance actions, ii) which are the SDGs most negatively affected by poverty, and iii) which are the main challenges for the implementation of SDG 1. An international survey was performed with researchers, professors, and representatives of administrative sectors in universities from 34 countries round the world. The vast majority of those taking part in the study consider poverty to be a threat to the implementation of the SDGs in their countries. Practically all goals are seen to be hampered, especially SDG 2 'Zero Hunger', SDG 3 'Good Health and Well-being', SDG 4 'Quality Education' and SDG 6 'Clean Water and Sanitation'. The implications of this paper are twofold: it illustrates the need to pay a special attention to poverty reduction which may pose a central barrier to the implementation of the SDGs and describes a set of items needed, in order to foster the implementation of one of the key goals. Highlights: An exploratory study on the relation of poverty and the implementation of SDGs. All goals are impacted, particularly the ones on hunger, health, education, and water. Main challenges for the implementation of SDG 1 are discussed.